The Effect of Nutrition combination Ab-Mix and fermented cow urine To Growth and Results Mustard of Hydroponic Culture - abdul syukur; setia budi; nurjani . (Fakultas Pertanian Universitas Tanjungpura, 2020)
This research was conducted to determine the combination of ab-mix nutrients and fermented cow urine for growth and results mustard of hydroponic culture. This research was conducted in the district Ngabang in district Landak West Kalimantan which lasted 13 January until 23 February 2019. The method used is the complete randomized design (CRD) consisted of 6 treatments, 4 replitions, and 6 sampling unit plants. The combination of ab-mix nutrients and fermented cow urine where P1 = 5 ml Ab-Mix/L solution, P2 = 2.5 ml Ab-Mix + 50 ml fermented cow urine/L solution, P3 = 2.5 ml Ab-Mix + 60 ml fermented cow urine/L solution, P4 = 2.5 ml Ab-Mix + 70 ml fermented cow urine/l solution, P5 = 2.5 ml Ab-Mix + 80 ml fermented cow urine/L solution and P6 = 90 ml of fermented cow urine/L solution. Variable observations in this research were plant height, number of leaves, area of leaf, plants fresh weight, plants dried weight, and the volume of roots. The results showed that combination of nutrients ab-mix and fermented cow urine had a significant effect on all observation variables, the best treatments of control 5 ml ab-mix/L solution, lowest treatment of control 90 ml of fermented cow urine/L solution and the best combination treatment 2.5 ml Ab-Mix + 80 ml fermented cow urine/L solution. Keywords : Ab-mix goodplant, cow urine is fermented, hydroponics, Mustard.